2008
DOI: 10.1039/b812396a
|View full text |Cite
|
Sign up to set email alerts
|

Polyfunctional benzylic zinc chlorides by the direct insertion of magnesium into benzylic chlorides in the presence of LiCl and ZnCl2

Abstract: Benzylic zinc chlorides bearing various functional groups are smoothly prepared by the direct insertion of magnesium into benzylic chlorides in the presence of LiCl and ZnCl(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 20 publications
0
42
0
10
Order By: Relevance
“…Quenching of the functionalized benzylic zinc reagents 13 with various electrophiles (E + ) provides a range of benzylic derivatives of type 16 (Scheme 6). [11] Although Zn in the presence of LiCl [8c, 26] also leads to a smooth reaction with various benzylic chlorides, the use of a more strongly reducing metal such as magnesium allows faster insertion times. Thus, treatment of 4-fluorobenzyl chloride (14 a) with Zn powder (2.0 equiv) in the presence of LiCl (2.0 equiv) provides the corresponding zinc reagent 13 a after a reaction time of 24 h at 25 8C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quenching of the functionalized benzylic zinc reagents 13 with various electrophiles (E + ) provides a range of benzylic derivatives of type 16 (Scheme 6). [11] Although Zn in the presence of LiCl [8c, 26] also leads to a smooth reaction with various benzylic chlorides, the use of a more strongly reducing metal such as magnesium allows faster insertion times. Thus, treatment of 4-fluorobenzyl chloride (14 a) with Zn powder (2.0 equiv) in the presence of LiCl (2.0 equiv) provides the corresponding zinc reagent 13 a after a reaction time of 24 h at 25 8C.…”
Section: Resultsmentioning
confidence: 99%
“…[10] We have also reported that in the case of substrates bearing sensitive functional groups, the highly reactive magnesium intermediates can be efficiently trapped in situ by ZnCl 2 , leading to polyfunctional zinc compounds of type 4 (Scheme 1). [10,11] Herein, we wish to report the scope and limitations of this efficient insertion of magnesium into aryl, heteroaryl, and benzylic bromides (or chlorides). A new orthogonal regioselectivity pattern of zinc and magnesium insertions is also disclosed.…”
Section: Introductionmentioning
confidence: 99%
“…Functionalized alkylzinc bromides [56] such as 30-33 (Scheme 4.7), as well as benzylzinc chlorides [55,57], can be prepared starting from the corresponding organic halides through in situ reduction involving Mg(0) in the presence of Zn(II) salts.…”
Section: Transmetallation Reactions With Main-group and Transition Mementioning
confidence: 99%
“…Auch die Verwendung von Lewis-Säuren kann nçtig sein, um die Reaktivität dieser Metallreagentien zu erhçhen. [52] An dieser Stelle soll auch die Kompatibilität von Arylund Heteroaryl-Zink-, Kupfer-und Indium-Reagentien mit aziden Protonen betont werden. Diese Toleranz gegenüber OH-und NH-Gruppen wurde besonders ausführlich in Bezug auf Organozinkreagentien untersucht.…”
Section: Die Frage Der Chemoselektivitätunclassified
“…eine sekundäre Alkoholfunktion tragen. [52,53] Das Zinkreagens 36 wird vorzugsweise über 90 min zu einem Gemisch aus sekundärem Alkohol und dem Katalysatorsystem zugegeben (Schema 9).…”
Section: Die Frage Der Chemoselektivitätunclassified